Hypotensive therapy of a comorbid patient: what is the basis for choosing the right drug? - A. S. Skotnikov; D. Yu. Yudina; E. Yu. Stakhnev (Лечащий Врач)
The article considers approaches to selection of hypotensive therapy for different categories of patients, on the basis of age-, sex-, gender-related (social) characteristics of the patients, as well as the range of risk factors and nosological units in the structure of comorbidity.